A customized program for the identification of conserved protein sequence motifs - Mohammad Mian; Jeffrey Talada; Anthony Klobas; Stephanie Torres; Yusuf Rasheed; Hibah Javed; Zainab Lughmani; Reza Forough (BioTechniques)
We searched for viral protein sequences that could be important for tissue tropism. To achieve this goal, human pathogenic viruses were classified according to the tissue they infect (e.g., pulmonary), irrespective of whether they were enveloped or non-enveloped RNA or DNA viruses. Next, we developed an amino acid sequence alignment program and identified the conserved amino acid motif, VAIVLGG, in alphaviruses. The VAIVLGG sequence is located on the structural capsid protein of the chikungunya virus, a mosquito-borne arthrogenic member of the alphaviruses. Capsid protein translocation onto the host cell membrane is a required step for virion budding. Our identified VAIVLGG consensus sequence might potentially be used for developing a pan-vaccine effective against alphaviruses.